THE ISRA'ILIYYAT NARRATIVES IN THE BOOK AL-DURR AL-MANTHUR FI TAFSIR AL-MA'THUR - Siti Aldasari Dwi Rohmawati Almurod; Abu Bakar Yamani (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2024)
Al-Asil and al-Dakhil are among the relatively new areas of study within Qur'anic studies. Al-Asil refers to interpretive sources that are considered valid and accountable, while al-Dakhil means anything suspected to be an intrusion into interpretation and thus should be avoided and removed. The study of al-Asil and al-Dakhil is often used to identify Isra'iliyyat traditions that commentators have included in their works of interpretation. The inclusion of Isra'iliyyat is intended to uncover the hidden meanings behind the stories in the Qur’an, considering that the Qur’an often presents them in a general manner. In this article, an analysis will be conducted on the Isra'iliyyat traditions within the al-Durru al-Manthur fi Tafsir al-Ma'thur by Jalal al-Din al-Suyuti. If these traditions conflict with Islam, they are classified as dakhil; conversely, if they align or do not conflict, they are classified as asil. The methodology employed is a descriptive-analytical method commonly applied in qualitative research models. In his interpretation, al-Suyuti cites twenty-two traditions while interpreting Surah al-Isra’, verse 4, verse 44, and verse 55. After analysis, it was found that seventeen of these are considered asil, and the remaining five are classified as dakhil due to their inconsistency with the interpretations of most commentators.